Modulation and coding for wireless communications - Burr, Alister (Prentice Hall, 2001)
"Modulation and Coding for Wireless Communications is an authoritative, modern text on two interrelated and increasingly important topics within communications engineering. This text will provide a useful reference to modulation and coding as well as a review of current practice. Accessibly written, this will be a suitable textbook for students on advanced communications engineering courses as well as an important